In vivo molecular imaging of chemokine receptor CXCR4 expression in patients with advanced multiple myeloma - Kathrin Philipp‐Abbrederis; Ken Herrmann; Stefan Knop; Margret Schottelius; Matthias Eiber; Katharina Lückerath; Elke Pietschmann; Stefan Habringer; Carlos Gerngroß; Katharina Franke; Martina Rudelius; Andreas Schirbel; et al. (EMBO Molecular Medicine)
Abstract CXCR4 is a G‐protein‐coupled receptor that mediates recruitment of blood cells toward its ligand SDF‐1. In cancer, high CXCR4 expression is frequently associated with tumor dissemination and poor prognosis. We evaluated the novel CXCR4 probe [68Ga]Pentixafor for in vivo mapping of CXCR4 expression density in mice xenografted with human CXCR4‐positive MM cell lines and patients with advanced MM by means of positron emission tomography (PET). [68Ga]Pentixafor PET provided images with excellent specificity and contrast. In 10 of 14 patients with advanced MM [68Ga]Pentixafor PET/CT scans revealed MM manifestations, whereas only nine of 14 standard [18F]fluorodeoxyglucose PET/CT scans were rated visually positive. Assessment of blood counts and standard CD34+ flow cytometry did not reveal significant blood count changes associated with tracer application. Based on these highly encouraging data on clinical PET imaging of CXCR4 expression in a cohort of MM patients, we conclude that [68Ga]Pentixafor PET opens a broad field for clinical investigations on CXCR4 expression and for CXCR4‐directed therapeutic approaches in MM and other diseases.